2020
DOI: 10.1038/s41467-019-13809-8
|View full text |Cite|
|
Sign up to set email alerts
|

Ketamine disinhibits dendrites and enhances calcium signals in prefrontal dendritic spines

Abstract: A subanesthetic dose of ketamine causes acute psychotomimetic symptoms and sustained antidepressant effects. In prefrontal cortex, the prevailing disinhibition hypothesis posits that N-methyl-d-aspartate receptor (NMDAR) antagonists such as ketamine act preferentially on GABAergic neurons. However, cortical interneurons are heterogeneous. In particular, somatostatin-expressing (SST) interneurons selectively inhibit dendrites and regulate synaptic inputs, yet their response to systemic NMDAR antagonism is unkno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
84
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(96 citation statements)
references
References 71 publications
11
84
0
1
Order By: Relevance
“…However, the measurable NM-DAR conductances within PV interneurons are relatively small in comparison to other MGE subtypes [12]. Additionally, NMDA signaling in non-PV interneuron subtypes drives robust dendritic inhibition in pyramidal neurons [114, 115]. Moreover, while NMDAR-ablation in Pvalb -Cre lines produces other behavioral deficits unrelated to the Sz-like phenotypes [30, 33], a developmental, but not adult-onset Grin1 -ablation in Ppp1r2 -Cre line [29] that targets a subset of PV interneurons among other subtypes [116], recapitulates core Sz-like phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the measurable NM-DAR conductances within PV interneurons are relatively small in comparison to other MGE subtypes [12]. Additionally, NMDA signaling in non-PV interneuron subtypes drives robust dendritic inhibition in pyramidal neurons [114, 115]. Moreover, while NMDAR-ablation in Pvalb -Cre lines produces other behavioral deficits unrelated to the Sz-like phenotypes [30, 33], a developmental, but not adult-onset Grin1 -ablation in Ppp1r2 -Cre line [29] that targets a subset of PV interneurons among other subtypes [116], recapitulates core Sz-like phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, ketamine rapidly decreases GABAergic synaptic transmission onto hippocampal CA1 pyramidal neurons (Widman and McMahon, 2018). Ketamine more effectively inhibits the NMDARs on GABAergic interneurons than those on pyramidal neurons, resulting in decreased firing of interneurons and subsequent bursting of pyramidal neurons (Homayoun and Moghaddam, 2007;Duman et al, 2016;Ali et al, 2020). These findings suggest that the rapid antidepressant effect of ketamine is attributable (either in full or in part) to the enhanced E/I ratio caused by disinhibition.…”
Section: Discussionmentioning
confidence: 97%
“…While ketamine impacts glutamatergic transmission directly in the HPC, these effects are indirect in the mPFC given that, here, ketamine acts directly on GABAergic transmission. Reports have implicated PFC GABAergic interneurons, specifically somatostatin-expressing (SST) interneurons, in controlling ketamine’s antidepressant effects (Fuchs et al, 2017 ; Ali et al, 2020 ; Gerhard et al, 2020 ). Within the PFC, SST interneurons act as a microcircuit to provide inhibitory control over glutamatergic excitatory pyramidal neurons (Kepecs and Fischell, 2014 ).…”
Section: Ketamine As a Potential Aud Treatment Optionmentioning
confidence: 99%
“…Furthermore, it has been shown that the disinhibition of PFC pyramidal neurons through knockdown of GABA A receptors on SST interneurons produced antidepressant and anxiolytic effects in mice, indicating that SST interneurons may be a prime target for antidepressant effects (Fuchs et al, 2017 ). A recent study used calcium (Ca 2+ ) imaging to show that ketamine inhibited SST interneurons in the mPFC, which led to the disinhibition of mPFC pyramidal neurons and enhanced glutamatergic transmission (Ali et al, 2020 ). Importantly, two reports have shown that ketamine’s effect on SST inhibition was through NMDAR antagonism since it was dependent upon the GluN2B subunit of the NMDAR (Ali et al, 2020 ; Gerhard et al, 2020 ).…”
Section: Ketamine As a Potential Aud Treatment Optionmentioning
confidence: 99%